Impact of Intimate Partner Violence on Self Esteem of Women in Pakistan - Tariq, Qudsia (American Journal of Humanities and Social Sciences, 2013)
The aim of this research was to investigate the impact of intimate partner on the self esteem of women .Since this was a very sensitive area henceforth the triangulation method was used for in-depth study A purposeful sampling was applied after the screening of the participants with the help of HITS (Kevin) The sample included 118 abused women and 98 of them were not abused. The instruments were translated into the native language to commune well with the participants. Both the scales i.e. HITS (Kevin), and Rosenberg self-esteem scales, were translated. The Qualitative Findings suggest that factors like economic dependence, insecurity social pressures, were the general themes concluded from the transcripts for the low self esteem of an abused women .The Quantitative data analysis indicated that the self esteem of the psychologically and physically abused was more shattered then the not abused women the t-test calculated and found to be significant as p <.05 There was one major limitation related to the size and representation from all the provinces to draw a clear view of the situation. This study can help in identifying the vulnerability level of women for future pathology and assist in developing a program for the rehabilitation of the victims by removing the barriers and helping them to cope well.